Makna Penderitaan Orang Benar dalam Perspektif Kedaulatan Allah: (Kajian Tafsir terhadap Kitab Ayub 1–2 dan 38–42) - Prayes Thelord; Monika Tumba' Ta'birara'; Arisa Patoding; Isa Pelicia (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2026)
This study uses a qualitative research design with a literature study approach to examine the theological meaning of the suffering of the righteous in the Book of Job, specifically chapters 1–2 and 38–42. The literature study method was applied by collecting primary data in the form of biblical texts and secondary data from relevant national scientific journals. The approach used includes narrative interpretation to understand the story's structure, Job's character, and the dynamics of events, and theological interpretation to interpret suffering from the perspective of God's sovereignty. The results show that Job is portrayed as a righteous man who is pious, honest, and fears God, so his suffering is not related to personal sin. Job's suffering is holistic, encompassing physical, emotional, social, and spiritual aspects, and occurs in the context of God's permission of Satan's actions, confirming that no event is outside His sovereignty. God's response in chapters 38–42 emphasizes His greatness and wisdom through revelation from the storm, rather than through a rational explanation of the cause of suffering. These findings confirm that the primary purpose of suffering is not to be explained intellectually, but to purify faith and deepen humanity's relationship with God. Its relevance for the church today lies in the need for sound theological teaching on suffering, pastoral care for those who suffer, and the development of communities that sustain the faith and hope of the congregation. Thus, suffering, from the perspective of God's sovereignty, serves as a means of forming spiritual character, strengthening the resilience of faith, and recognizing the sovereign God.